Negative resistance induced Terahertz generation and detection by strained channel MOSFETs: A simulation based analysis - Kumar M.; Jindal P.K.; Jit S. (My University, 2025)
This paper reports an ATLASTM TCAD-based three-dimensional (3D) simulation of the strained-Si on SSOI MOSFETs to explore the possibility of these devices for terahertz generation applications. The output current-voltage characteristics have been critically analyzed for various gate lengths, channel thickness and strain values in the channel of the device. Non-linear transient analysis are carried out to examine the possibility of the strained-Si SOI MOSFETs for terahertz generation applications. It has been found that increasing the channel's strain can enable the device to detect terahertz radiation at lower frequencies. This research can be used to create next-generation VLSI devices with s-Si SOI MOSFETs for terahertz photonics applications. © 2024 Author(s).